An Asian perspective on policy instruments: policy styles, governance modes and critical capacity challenges. Issue 1 (2nd January 2016) - Mukherjee, Ishani; Howlett, Michael
Abstract : Does Asia have a distinct policy style? If so, what does it look like, and why does it take the shape it does? This article argues that in the newly reinvigorated emphasis of policy studies on policy instruments and their design lies the basis of an analysis of a dominant policy style in the Asian region, with significant implications for understanding the roles played by specific kinds of policy capacities. There is a distinctly Asian policy style based on a specific pattern of policy capacities and governance modes. In this style, a failure to garner initial policy legitimacy in the articulation of instrument norms often results in later mismatches between instrument objectives and specific mechanisms for their achievement. The formulation of payments for ecosystem services policy is used to illustrate the capacities required for policy designs and action to meet policy goals effectively.